Assessment of primary health centres of a district in North Karnataka according to Indian Public Health Standards 2012 guidelines: a cross sectional study - Patil, Shrinivas K.; M. S., Shivaswamy (International Journal Of Community Medicine And Public Health, 2019)
Background: Primary health centre (PHC) is a basic health unit to provide an integrated curative and preventive health care to the rural population as close to the people as possible, with emphasis on preventive and promotive aspects of health care. Methods: A facility based cross-sectional study was conducted in Belagavi district of Karnataka in India. Twenty PHCs, two PHCs from each of the 10 talukas of Belagavi district were selected by simple random sampling. The study period was from 1st January 2014 to 31st December 2014. Data was collected using a predesigned and structured questionnaire for IPHS facility survey. Results: In this study, only 60% of primary health centres covered the population as per the IPHS norms. All the PHCs were providing the regular outpatient department (OPD) services, referral services, antenatal care, family planning and in-patient services. Bed occupancy rate was less than 40% in 55% of PHCs. Building area in 75% of PHCs were inadequate according to IPHS norms. Residential facility for staff was available only in half of the studied PHCs. Conclusions: IPHS guidelines were not fully being followed at PHC level in the district. Though the requirement of medical officers and pharmacists was fulfilled in almost all the PHCs, deficiency was seen in the appointing of Ayush doctors and staff nurses at PHCs. There is an urgent need of recruiting the deficient staff for efficient functioning of the PHCs.